A brief analysis of the Republic of Korea's defense reform plan - Bennett, Bruce W., 1952-; Rand eBooks (Santa Monica, CA : RAND, 2006)
At the request of Republic of Korea (ROK) Assemblyman Jin-Ha Hwang, a member of the National Assembly's National Defense Committee, this analysis was performed of the ROK Defense Reform Plan (DRP). It examines the overall nature of the DRP, identifies major risks in the plan, and discusses how those risks can be managed. It concludes that the DRP is a good approach to potential ROK security dilemmas, but the plan faces major risks, especially in meeting potential ROK security requirements. The DRP could be strengthened by adding concepts for managing its major risks. This paper discusses the background of the DRP and the manpower problem it needs to address. It then presents the author's estimates of the force changes that would occur and how those forces appear to fit the force requirements the ROK will likely face in the coming years. It examines the budget requested for the DRP and whether it will cover the necessary costs, addresses the effects that the DRP could have on ROK military morale and how the United States may view the DRP, and concludes by recommending steps the ROK could take to manage the key risks identified throughout this analysis.
"RAND National Defense Research Institute."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Military planning -- Korea (South); National security -- Korea (South); Korea (South) -- Defenses; Korea (South) -- Military policy; Korea (South) -- Strategic aspects; Electronic books